Seismic slope stability of a dike built on Singapore marine clay : a numerical study - Goh, Clayder Kan Sheng (2014)
An assessment of the seismic slope stability of a sand-filled dike built on soft coastal clay using pseudo-static analysis in PLAXIS 2D finite-element program is made, by comparing the static and dynamic factor of safety against sliding across 90 models representing 4 cases of interest. Sand dikes of final height of 12 m are subjected to PGA magnitudes of 0.013g and 0.025g during the staged construction. The soil profile of the Changi East Reclamation Project of 1991 is extracted. The magnitude of the expected sea level rise is considered to reflect local conditions. The degree of consolidation of the foundation soil and the slope gradient of the dike are varied for short-term analysis. In the interest of evaluating cost-effectiveness, slope trimming is simulated on a 1:6 gradient dike and stability results are compared with a 1:15 gradient dike. These dike models are then subjected to potential severe tidal conditions for long-term serviceability analysis. It is shown that ground tremors in Singapore are able to reduce slope stability up to 37.6%. An increase in the degree of consolidation does not produce significant increase in stability as expected. On the other hand, a gentler slope shows a more prominent increase in stability at higher PGA magnitudes. In addition, slope trimming produces substantial increase in both static and dynamic factor of safety than decreasing slope gradient. This offers slopes a higher capacity to resist strong ground motions in addition to tidal forces.